Horse Races and Polo Games of Mongolians (Tartars)
total panel #5 Constructed over the old temple of Wiracocha the Cathedral was initially of poor construction. Remodelling began in 1560. The Basque architect Manuel de Veramendi was in charge until 1654, and his successor Diego Arias de la Cerda finished the reconstruction.